(3GdfXGe GdbGfhfj ddGSJKeGQ GdCLfHj aj Gdjef (B: s (3OQGSI bGfhfjI ebGQfI (B/ s - (3MHjH GdQMef Ydj CMeO fGFas; (3eMehO eNJGQ CMeO HQHQj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2011)
(3jJeKd GdfXGe Gdbfhfj ddGSJKeGQ GdCLfHj aj GdbhGYO GdbGfhfjI h GdELQGFjI GdJi JVYgG GdOhdI GdeVjaI h JUOQgG Ydi UhQI JTQjYGJ bGfhfjI JgOa Edi LPH QDhS GdCehGd GdCLfHjI(B: (3h Pdc ef NdGd eG JbOeg ef JSgjdGJ eGdjI h EOGQjI h ef MhGaR VQjHjI h ZjQ VQjHjI(B: (3h eG JhaQg ef VeGfGJ ehVhYjI h ELQGFjI JdHj GdeJWdHGJ GdOhdjI h JhGcH GdeSJLOGJ h GdJWhQGJ GdeJSGQYI aj eLGdGJ GdGSJKeGQ h GdJLGQI h GdGbJUGO(B. (3h GdOhQ GdPj jdYHg GdLGfH GdJTQjYj aj JMSjf GdefGN GdGSJKeGQj dG jJeKd ajeG jMTOg ef eRGjG h MhGaR HbOQ eG jJeKd ajeG jYcSg ef SjGSI GSJKeGQjI JhGaQJ dgG CSHGH GdhVhM h GdGSJbQGQ(B: (3h JhGaQ ddefGN GdPj jQGO dg Cf jYed aj Xdg YfGUQg GdCNQjs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj, (B2011s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B545-582s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdGSJKeGQ GdCLfHjs; (3bGfhf GdGSJKeGQs; (3efGN GdGSJKeGQs; (3GdhVY GdGbJUGOj aj Gdjefs; (3GdMhGaR GdeefhMI ddGSJKeGQGJ GdCLfHjI aj Gdjefs; (3VeGfGJ MeGjI GdGSJKeGQGJ GdCLfHjIs; (3JShjI efGRYGJ GdGSJKeGQ aj GdefWbI GdMQIs; (3GdGJaGbjI GdehMOI dGSJKeGQ QDhS GdCehGd GdYQHjIs; (3eYhbGJ GdGSJKeGQ aj Gdjefs; (3GdgjFI GdYGeI ddGSJKeGQ aj Gdjefs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs